Review of Transport Vehicles on Ferry Board At Bira - Pamatata Tracking - A Agus Tjahjono; Bambang Setiawan; Rizky Putra Wijaya (IWJ : Inland Waterways Journal, 2019)
The ferry port of Bira are harbor crossings which serve traffic between provinces and between islands by crossing trajectory Bira - Labuan Bajoe and Bira - Pamatata. The ferry port of Bira is managed by the Regional Technical Implementation Unit (UPTD) the ferry port for infrastructure and PT.ASDP Indonesia Ferry (Persero) Branch Selayar to ingredients. The ferry port of Bira is closely associated with the economic development of the community because many people who do activities in the region and the Bulukumba district of Makassar and Selayar Island is an area (Hinterland) who really need both parts of clothing and food. In the security and safety of the transportation system highly favored as a form of good service delivery. Safety was shown not only to the service users, but also to the ship operator. As well as setting up and handling of cargo vehicles on board. The better regulation and vehicle handling on board the better the level of security and safety of vehicles on board and vice versa. The setting and handling of cargo vehicles on board is good for the service user / owner of the vehicle, as well as for the security and safety of vehicles on board and are not harmful to the operator of the vessel that can be done by means of an approach based on the arrangement of the vehicle by placing a distance between the vehicle safe and mounting strap vehicle (lashing) contained in the PM number 115 of 2016 on procedures for the transport of vehicles on board. As well as setting up and handling of cargo vehicles on board. The better regulation and vehicle handling on board the better the level of security and safety of vehicles on board and vice versa. The setting and handling of cargo vehicles on board is good for the service user / owner of the vehicle, as well as for the security and safety of vehicles on board and are not harmful to the operator of the vessel that can be done by means of an approach based on the arrangement of the vehicle by placing a distance between the vehicle safe and mounting strap vehicle (lashing) contained in the PM number 115 of 2016 on procedures for the transport of vehicles on board.